Influence of export promotion in the export development of MYPES in the Tacna region, period 2008 - 2009 - Loza Ticona, Renzi Marilu (2012)
This is a basic, descriptive correlational research work because it tries to determine the relationship between variables studied, namely: Promotion of exports and exports development. We considered information obtained through a questionnaire titled “Promotion of exports and exports development in Mypes in Tacna”. It was applied to 99 Exporting Mypes in Tacna Region. Our objective was to determine the influence of exports promotion in export development of MYPES in Tacna región in 2008-2009. Our most important results were: Exporting MYPES in Tacna Region have a low level of  knowledge on the benefits given by entitics in charge of export promotion. Exporting MYPES in Tacna Region have a lower level of Access to programs and services for export promotion every year. Strategic alliances with institutions that promote exporting are mainly towards information and training about exporting, advising about exports was also given. Also. the level of programs and services given by export institutions is very low. Therefore, the level of export development achieved by MYPES in Tacna region is low.